Soil conservation efficiency and improvement potential of forestry sector in China during 2006 to 2018 - Keke Li; Zhanhang Zhou; Hua Yan; Yanxian Li; Cai Li; Yuemin Yang; Wei Li; Zhen Wang (Sustainable Futures)
Forests are essential in alleviating the environmental burden imposed by economic development, especially in reversing the exacerbated trend of land degradation in China over the years. However, the spatial divergences in forestry efficiency for soil-conservation services and its dynamic changes remain unclear at the national scale. In this study, we evaluated the relative forestry efficiency in soil conservation efforts and revealed its improvement potential from a dynamic perspective by integrating the soil conservation datasets estimated by the Revised Universal Soil Loss Equation (RUSLE), Slack-Based Measure (SBM) model, and Malmquist index. Results showed that the nationwide soil conservation efforts in forested areas have been steadily increasing with a fluctuating upward trend of soil-conservation efficiency. Especially, southwestern China was identified as a hotspot region for soil conservation, contributing to about 30.3% of the total. It experienced the most significant increase in forestry efficiency from 2006 to 2018, mainly attributed to the progress of forestry resource utilization efficiency. In contrast, northern regions, which are also major areas for soil conservation, need to pay much more attention to advancing technological progress in soil conservation practices. Among variable forestry input indicators, the forestry financial investment showed a relatively high improvement potential. This calls for more effective financial allocation to optimize forestry efficiency. Evaluating the relative efficiency of forestry in soil conservation over the years offers dynamic insights for policymakers to optimize forestry management strategies in China, thereby enhancing both environmental and economic sustainability.